2018
DOI: 10.1519/jpt.0000000000000125
|View full text |Cite
|
Sign up to set email alerts
|

Physical and Nutritional Prehabilitation in Older Patients With Colorectal Carcinoma: A Systematic Review

Abstract: Physical and nutritional prehabilitation in older patients with CRC has not shown a significant reduction in postoperative complications or length of stay. One study that examined the effect of a perioperative nutritional supplement reported a reduction in postoperative complications. Future research should explore targeted combined interventions, taking into account physical and nutritional patient requirements.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 46 publications
(34 citation statements)
references
References 43 publications
1
33
0
Order By: Relevance
“…Future research needs to clarify the prognostic value of these measures in addition to CT‐based body composition measures over time, to predict the risk of adverse outcomes in older patients with CRC. This is also important in the development of preoperative interventions, also known as prehabilitation, which can be effective in older patients with CRC .…”
Section: Discussionmentioning
confidence: 99%
“…Future research needs to clarify the prognostic value of these measures in addition to CT‐based body composition measures over time, to predict the risk of adverse outcomes in older patients with CRC. This is also important in the development of preoperative interventions, also known as prehabilitation, which can be effective in older patients with CRC .…”
Section: Discussionmentioning
confidence: 99%
“…A burgeoning body of research is investigating the utility of preoperative interventions, known as prehabilitation, to optimize posttreatment health outcomes. Numerous reviews of the prehabilitation literature in cancer populations demonstrate several important benefits, including improved preoperative and postoperative physical function, reduced hospital length of stay, and fewer postoperative complications (18)(19)(20)(21)(22)(23)(24). However, this literature exists almost exclusively in people undergoing tumor resection for thoracoabdominal malignancies, with breast cancer prehabilitation remaining largely unexamined.…”
Section: Introductionmentioning
confidence: 99%
“…No significant effect of the protein‐rich meal service at home was found on nutrition status, hand grip strength, SPPB, quality of life, complications, or LOS, which is in line with studies on home‐delivered meal services 31 . It is suggested that combining a nutrition intervention (energy‐, protein‐, and/or carbohydrate supplements) with exercise (resistance and aerobic) could be effective to improve physical and clinical outcomes, but sufficient evidence is lacking 32,33 . A recent review on patients with colorectal cancer concluded that such prehabilitation programs have not shown a significant reduction of complications or hospital LOS 32 .…”
Section: Discussionmentioning
confidence: 60%